Hubungan Tingkat Pengetahuan Kesehatan Reproduksi Remaja dengan Sikap Seksual Pranikah Siswa Kelas XI SMK 2 Batam - Ridni Husnah; Nuari Andolina; Hikma Fajar Cahyani (Journal on Education, 2021)
Uninhabitable Pregnancy (KTD) that occurs in married women and in remja is one of the cases that can affect the high mortality rate in women. One of the causes of unwanted pregnancy is premarital sexual behavior, before the existence of premarital sexual behavior a negative (supportive) sexual attitude is formed. One of the factors in the formation of attitudes is educational institutions and religious institutions. Limited knowledge in adolescent reproductive health results in negative premarital sexual attitudes. The purpose of this study was to determine the relationship between adolescent reproductive health knowledge and premarital sexual attitudes at SMK 2 Batam. This research method is an Analytical Survey, a type of research using Observational with a cross-sectional time approach, sampling using purposive sampling, namely what the subjects used in the case were 80 adolescents who had met the inclusion and exclusion criteria, data collection used questionnaires and distributed to respondents, analyzed using univariate and bivariate analysis using chi square analysis. The results of the study there was a significant relationship between adolescent reproductive health knowledge and premarital sexual attitudes, p-value 0.000 (α = 0.05). This study can be concluded that there is a significant relationship between the level of knowledge of adolescent reproductive health and premarital sexual attitudes.